Malay Interrogative Sentences: X-Bar Analysis - Gumarpi Rahis Pasaribu; Mulyadi (RETORIKA: Jurnal Ilmu Bahasa, 2023)
This study examines the syntactic behavior of question words of malay in the interrogative construction in north labuhanbatu. This study aimed to analyze the question words of all interrogative types in the language. Therefore, the research data cover question words known as word malay in north labuhanbatu which are derived from the relevant literature. The theoretical framework used in this study is the X-bar theory proposed by Haegeman (1992). The data analysis techniques used in this research were distributed methods which use the language element determination tool itself. The results show that the malay north labuhanbatu partial sentence has a grammatical and complementary grammatical function, while the total question sentence has a complement function. Malay question words can be constructed by specifier, complements, and adverbials. The Malay question sentence formed by specifier functions as an internal structure occupied by the NP and joined by I’ to form an IP. Furthermore, the question words formed by complement functions as an internal structure occupied by PP or NP and joined by V to form the first V'. Finally, the question words formed by adverbial functions as an internal structure that can be occupied by PP or NP to join the first V' then form the second V'.